Effect of nanoporous TiO2 coating and anodized Ca2+ modification of titanium surfaces on early microbial biofilm formation - Wennerberg Ann; Linderbäck Paula; Fröjd Victoria; Chávez de Paz Luis; Svensäter Gunnel; Davies Julia R (BMC, 2011)
Abstract Background The soft tissue around dental implants forms a barrier between the oral environment and the peri-implant bone and a crucial factor for long-term success of therapy is development of a good abutment/soft-tissue seal. Sol-gel derived nanoporous TiO2 coatings have been shown to enhance soft-tissue attachment but their effect on adhesion and biofilm formation by oral bacteria is unknown. Methods We have investigated how the properties of surfaces that may be used on abutments: turned titanium, sol-gel nanoporous TiO2 coated surfaces and anodized Ca2+ modified surfaces, affect biofilm formation by two early colonizers of the oral cavity: Streptococcus sanguinis and Actinomyces naeslundii. The bacteria were detected using 16S rRNA fluorescence in situ hybridization together with confocal laser scanning microscopy. Results Interferometry and atomic force microscopy revealed all the surfaces to be smooth (Sa ≤ 0.22 μm). Incubation with a consortium of S. sanguinis and A. naeslundii showed no differences in adhesion between the surfaces over 2 hours. After 14 hours, the level of biofilm growth was low and again, no differences between the surfaces were seen. The presence of saliva increased the biofilm biovolume of S. sanguinis and A. naeslundii ten-fold compared to when saliva was absent and this was due to increased adhesion rather than biofilm growth. Conclusions Nano-topographical modification of smooth titanium surfaces had no effect on adhesion or early biofilm formation by S. sanguinis and A. naeslundii as compared to turned surfaces or those treated with anodic oxidation in the presence of Ca2+. The presence of saliva led to a significantly greater biofilm biovolume but no significant differences were seen between the test surfaces. These data thus suggest that modification with sol-gel derived nanoporous TiO2, which has been shown to improve osseointegration and soft-tissue healing in vivo, does not cause greater biofilm formation by the two oral commensal species tested than the other surfaces.